Spontaneous cortical activity transiently organises into frequency specific phase-coupling networks - Vidaurre, D (University of Oxford, 2018)
As part of the UK MEG Partnership, 77 healthy participants were recruited at the University of Nottingham. All participants gave written informed consent and ethical approval was granted by the University of Nottingham Medical School Research Ethics Committee. A final cohort of 55 participants (mean age 26.5y, maximum age 48y, minimum age 18y, 35 males) was selected for analysis, discarding 22 subjects because of excessive head motion or artefacts. To avoid effects of tissue magnetisation, MEG data were acquired prior to participants entering the MRI. Resting-state MEG data were acquired using a 275-channel CTF MEG system (MISL, Coquitlam, Canada) operating in third-order synthetic gradiometry configuration, at a sample frequency of 1200Hz. MRI data, used here for the purpose of MEG coregistration, were acquired using a Phillips Achieva 7T system. MEG data were then downsampled to 250Hz using an anti-aliasing filter, filtered out frequencies below 1Hz, and source-reconstructed using LCMV beamforming24 to 42 dipoles covering the entire cortex excluding subcortical areas. Thirty-eight of these dipoles were obtained from a ICA decomposition on resting-state fMRI data from the Human Connectome Project, used previously to estimate large-scale static functional connectivity networks in MEG; the other four parcels correspond to the anterior and posterior precuneus which we wanted to disambiguate from the PCC given the importance of this region in the resting state, and the left and right intraparietal sulci. Bad segments were removed manually and correction for spatial leakage was applied. In order to project the results to brain space, we used a weighted mask, where each region had its maximum value at the center of gravity.